A Critical Overview on Development- Welfare, Power or Domination (Research Nepal Journal of Development Studies, 2019)
Development is quite a mixture approach as well as a continuous process. It serves as a mirror of changing economic and social capacities, and choices to make development more democratic and sustainable. The post-development paradigm sees all modern concept of development has been failed. Nepal cannot be exceptional from it, as it is struggling towards modernization and development, although some human development indexes seem to be improved. However, the discourse on development has frequently been questioned in Nepal due to its slow pace. Meanwhile, East Asia or China, Asia-Pacific countries changed such assumptions making huge economic progress. Therefore, it will be wrong to blame that the development has completely been failed. It is true that the globalization and advancement in technology have also created complexities worldwide and traditional approach of development may not work effectively because many new social, economic and environmental issues and problems have been raised over decades. The proper approach must consider the existing global context for sustainability and humanity, but not only domination of elites. Presently, good governance and people-centric issues have become a crucial part for the development. To make development more acceptance and sustainable, genuine and rational issues which are relating to human and environment must be considered. This paper aims to analyze the development approaches based on historical approach analyzing the past developments and reviewing development theories and make some suggestions for its suitability.